CIGR ejournal - International Commission of Agricultural Engineering (The Commission, 1999)
Provides research results and information in agricultural engineer. Provides an international forum for the scientific discussion of techniques and approaches leading to a higher degree of efficiency in agricultural production, the responsible use of natural resources, a cleaner environment, greater sustainability, value-added processing and other subjects of interest to agricultural engineers. Includes economic considerations and policy issues of interest to agricultural engineers.
Keywords: Agricultural engineering : Periodicals; Agricultural engineering